Evaluation of goal kicking performance in international rugby union matches. Issue 2 (March 2015) - Quarrie, Kenneth L.; Hopkins, Will G.
Abstract Objectives Goal kicking is an important element in rugby but has been the subject of minimal research. To develop and apply a method to describe the on-field pattern of goal-kicking and rank the goal kicking performance of players in international rugby union matches. Design Longitudinal observational study. Methods A generalized linear mixed model was used to analyze goal-kicking performance in a sample of 582 international rugby matches played from 2002 to 2011. The model adjusted for kick distance, kick angle, a rating of the importance of each kick, and venue-related conditions. Results Overall, 72% of the 6769 kick attempts were successful. Forty-five percent of points scored during the matches resulted from goal kicks, and in 5.7% of the matches the result of the match hinged on the outcome of a kick attempt. There was an extremely large decrease in success with increasing distance (odds ratio for two SD distance 0.06, 90% confidence interval 0.05–0.07) and a small decrease with increasingly acute angle away from the mid-line of the goal posts (odds ratio for 2 SD angle, 0.44, 0.39–0.49). Differences between players were typically small (odds ratio for 2 between-player SD 0.53, 0.45–0.65). Conclusions The generalized linear mixed model with its random-effect solutions provides a tool for ranking the performance of goal kickers in rugby. This modelling approach could be applied to other performance indicators in rugby and in other sports in which discrete outcomes are measured repeatedly on players or teams.